Students’ Sentence Errors on WhatsApp Daily Status: A Literature Review - Ulan Rindayan Saputra; Maulina Maulina; Rahmat Nasrullah; Geminastiti Sakkir (Har Press Indonesia, 2021)
The rapid development of social media affects all sectors of human life globally. In the education field, students can take advantage to improve their English skills through social media. Social media like WhatsApp enables students to gain valuable inputs because of its friendly use features. WhatsApp is allowing its users to send pictures, video, and text through the internet connection. To practice comprehensive English writing skills, WhatsApp facilitates students to improve their English skills through writing and updating daily status. This research discusses the data about students’ sentence errors when they create an English story on WhatsApp. The data obtained from e-Perpusnas, research gate, science direct, and Google scholar. Interlingual and intralingual factors are error sources of students’ WhatsApp daily status. Therefore, students can reduce or avoid errors in sentence development share a piece of information in English correctly and adequately.